Rights retention, open licensing and copyright: Reforming the policy landscape - Proudman, Vanessa; Treadway, Jon (Septentrio Conference Series, 2022)
Watch the VIDEO. Europe has seen a significant growth in Open Access (OA) policies but reform of copyright, licensing and rights retention has not followed or kept pace. Research funders such as the Horizon Europe programme and cOAlition S require authors to retain publishing rights to enable broad sharing of work under openly licenses. National policies have been set up in France, Spain and the Netherlands. Umbrella organizations like LIBER have called for legislation on the use of publicly funded scholarly publications. The European Commission is discussing this challenging area with experts to better enable Open Science. Some publishers have adopted recommended language wholesale, but more often their copyright policies stand in opposition to funder requirements, meaning authors are left to navigate the complexity and tension created. A number of institutions, in the UK, Norway and Germany are putting in place policies and support mechanisms for authors, while others are piloting rights retention actions. Stichting IFLA Foundation Programme, in partnership with IFLA, LIBER and SPARC Europe are implementing a three-year Arcadia Foundation-funded programme to reform copyright laws and regulations that enable libraries to provide significantly improved access to and use of copyrighted works. Knowledge Rights 21 aims to promote change at European, national and local levels by accelerating the uptake of rights retention and open licensing. It will do this by calling for action and change on behalf of publishers, institutions and funders to empower authors to retain their IP putting in needed resources to take key stakeholders to a new paradigm where copyright supports Open Science. The first year of the five year KR21 project is focused on building an evidence-base around current policies on copyright and licensing, and SPARC Europe is leading the sub-project on rights retention called Project Retain. It will aim to establish baselines and trends that can be monitored in subsequent years. The research will seek to better understand researcher motivations and how these are understood and being interpreted by policymakers. It will utilize interviews, surveys and focus groups to build a picture of what policies and processes publishers, funders and research institutions have put in place across Europe, drawing attention to the drivers and blockers of progress, and offering insight into good practice and innovative approaches. It will also build upon a 2020 SPARC Europe study which looked at provided copyright policies of large commercial publishers and numerous smaller ones showing where these do not meet funder requirements, and the complexities that authors faced publishing OA but not necessarily retaining their copyright. We will highlight policy change since that time. Our presentation will provide headlines generated by the research to understand the status of policies amongst publishers, institutions and funders. It will set out early thinking on recommendations for action and change arising from the research. We will then seek input from delegates through discussion and brainstorming to refine our interpretation and potential avenues for progress.